Status Trofik Ikan Karang dan Hubungan Ikan Herbivora dengan Rekrutmen Karang di Perairan Pulau Pari, Teluk Jakarta - Kunto Wibowo; Muhammad Abrar; Rikoh M. Siringoringo (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Trophic Status of Reef Fishes and Correlation between Herbivorous Fishes and Coral Recruitment in Pari Island Waters, Jakarta Bay. Species diversity and abundance of reef fishes is one of the indicators about the health of the reef ecosystem. Based on its trophic status, herbivorous fishes become an important group to control algae populations which are spatially coral competitors. This study aimed to determine the condition of reef fish species diversity in Pari Island waters and the relation between herbivorous fishes and coral recruitment. The study was conducted at five stations of coral reef ecosystems in Pari Island and surrounding areas in March 2014. Reef fish data collection was done by underwater observation using belt transects along 70 m length and 5 m width. Coral recruitment was recorded using transects of 1 x 1 m2, repeated 9 times. As many as 121 species of reef fishes belonging to 25 genera and 20 families were recorded. Pomacentridae, Labridae, and Chaetodontidae were three families with the highest species diversity. The abundance of herbivorous fishes varied among stations, from 4 to 52 individuals in each transect. Coral recruitment in Pari Island waters were low, i.e. 3.22 colonies/m2. However, the regression results indicated that the abundance of herbivorous fishes was positively correlated with the density of young corals. Herbivorous fish abundance and density of young corals in Pari Island waters have yet to show the maximum potential for reef recovery after damage. The low coral recruitment in the ecosystem of Pari Island waters was also caused by sedimentation, temperature, flow patterns, and salinity.